La competencia de los abogados, graduados en la Utmach, en defensa de los derechos humanos. - Romero Ortiz, Piero Rubén (Machala, 2020)
This title work is a bibliographic research that has as its theme, Competence of legal professionals graduated in the UTMACH of the last three promotions in defense of human rights, where it has been assigned as a general objective, evaluate the actions of these professionals by reviewing the legal processes, to determine whether the rights violated are being enforced and above all the professional ethics that regulate the activities that it carried out , himself within the framework of his profession. In addition, that the principle of orality is currently practiced in the justice system, which helps professionals entitled to better express their claims and to seek the restitution of the infringed right and corresponding compensation for their clients and to achieve judicial excellence. In our society, we are witnesses that at the national and international level the rights of human beings are constantly violated, that is where lawyers must ensure and enforce the rights guaranteed by the state of each nation and implement learning, with the purpose of improving professional practice. Since the amendment of Ecuador's constitution in 2008 in Montecristi, in the government of the citizen revolution, the Ecuadorian state aimed towards a more humanistic course, since rights were implemented specifically to provide a full life for the inhabitants of the nation and seek good living or Sumak kawsay, thus Ecuador being one of the first countries in Latin America to make its constitution more attached to ensuring the rights Human. In the administration of justice especially the role played by judges is of great importance since they must guarantee the principle of due process and effective judicial protection in each case that is dealt with in their office, in order to eradicate and reassess the violation of the rights that have been committed. In this analysis, the regulations provided for in the Constitution of the Republic of Ecuador or Magna Carta and the International Conventions on Human Rights, where the defence of human rights will be ensured, is fundamental. It is also important to mention that Ecuador is part of the United Nationals Organization, a body responsible for ensuring these inherent rights to human beings without discrimination on the property by nationality, sex, religion, language or otherwise. To complete the research it is necessary to use the following methodology that will be used to develop this research which will be: the exegetic; the one that allows to know the legal, explanatory vocabulary; allows to explain what happens, deductive deductive inductive; allows to analyze in general the particular and vice versa, comparative; compare similarities and differences, systematic; will allow the investigation to be worked on in an orderly manner following a procedure, analytical; understands what research analysis is. Likewise, techniques such as interview, survey, observation, among others, methods such as techniques that will be of great contribution and help to achieve completed success of this research will be used.
El presente trabajo de titulación es una investigación bibliográfica que tiene como tema, Competencia de profesionales del derecho graduados en la UTMACH de las últimas tres promociones en defensa de los derechos humanos, dónde se ha asignado como objetivo general, evaluar el accionar de estos profesionales mediante la revisión de los procesos jurídicos, para lograr determinar si se está haciendo respetar los derechos vulnerados y sobre todo la ética profesional que es la que regula las actividades que realizara, él mismo en el marco de su profesión. Además, de que actualmente en el sistema de justicia, se practica el principio de oralidad, lo que ayuda a los profesionales en derecho a expresar mejor sus pretensiones y a solicitar la restitución del derecho vulnerado e indemnizaciones correspondientes para sus clientes y poder lograr la excelencia judicial. En nuestra sociedad, somos testigos que a nivel nacional e internacional se viola constantemente los derechos de los seres humanos, es ahí donde los abogados deben velar y hacer respetar los derechos garantizados por el estado de cada nación y poner en práctica el aprendizaje, con el propósito de mejorar la praxis profesional. A partir de la modificación de la constitución del Ecuador en el año 2008 en Montecristi, en el gobierno de la revolución ciudadana, el estado ecuatoriano apunto hacia un rumbo más humanístico, ya que se implementaron derechos específicamente a brindar una vida plena para los habitantes de la nación y buscar el buen vivir o Sumak kawsay, siendo así el Ecuador unos de los primeros países en latino américa en hacer su constitución más apegada a velar por los derechos humanos. En la administración de justicia especialmente el rol que desempeñan los jueces y juezas es de gran importancia ya que estos deben de garantizar el principio al debido proceso y la tutela judicial efectiva en cada causa que en su despacho se tramite, para lograr erradicar y subsanar la violación de los derechos que se haya cometido. En este análisis es fundamental la normativa contemplada en la Constitución de la República del Ecuador o carta magna y en los Convenios Internacionales de Derechos Humanos, en dónde se garantizará la defensa de los derechos humanos. Es importante mencionar también que el Ecuador forma parte de la Organización de las Nacionales Unidas, organismo encargado de velar por estos derechos inherentes a los seres humanos sin discriminación alguna por su nacionalidad, sexo, religión, lengua u otra. Para completar la investigación resulta necesario recurrir a la siguiente metodología que se utilizará para elaborar esta investigación las cuales serán: el exegético; el que permite conocer el vocabulario jurídico, explicativo; permite dar explicación de lo que sucede, inductivo deductivo; permite analizar de lo general lo particular y viceversa, comparativo; comparar semejanzas y diferencias, sistemático; permitirá trabajar de manera ordena la investigación siguiendo un procedimiento, analítico; comprende lo que es el análisis de la investigación. De igual manera se utilizarán técnicas tales como la entrevista, encuesta, observación, entre otras, métodos como técnicas que serán de gran aporte y ayuda para lograr terminaron éxito la presente investigación.
Keywords: DERECHO HUMANO; COMPETENCIA PROFESIONAL; ADMINISTRACION DE JUSTICIA